Molecular mechanisms and cellular functions of liquid-liquid phase separation during antiviral immune responses - Yang, Shuai; Shen, Weishan; Hu, Jiajia; Cai, Sihui; Zhang, Chenqiu; Jin, Shouheng; Guan, Xiangdong; Wu, Jianfeng; Wu, Yaoxing; Cui, Jun (Frontiers in Immunology, 2023)
Spatiotemporal separation of cellular components is vital to ensure biochemical processes. Membrane-bound organelles such as mitochondria and nuclei play a major role in isolating intracellular components, while membraneless organelles (MLOs) are accumulatively uncovered via liquid-liquid phase separation (LLPS) to mediate cellular spatiotemporal organization. MLOs orchestrate various key cellular processes, including protein localization, supramolecular assembly, gene expression, and signal transduction. During viral infection, LLPS not only participates in viral replication but also contributes to host antiviral immune responses. Therefore, a more comprehensive understanding of the roles of LLPS in virus infection may open up new avenues for treating viral infectious diseases. In this review, we focus on the antiviral defense mechanisms of LLPS in innate immunity and discuss the involvement of LLPS during viral replication and immune evasion escape, as well as the strategy of targeting LLPS to treat viral infectious diseases.